Formulation, Phytochemical Characterization, and Clinical Assessment of a Novel Natural Supplement Targeting Body Composition in Physically Active Individuals: A Randomized Clinical Trial - Hama salih, Tablo Azad; Ali M. Farag, Halgord (Kurdistan Journal of Applied Research, 2025)
Nutritional supplementation plays a pivotal role in optimizing body composition, recovery, and performance in physically active individuals. This study aimed to evaluate the effects of an 8-week intervention with a novel natural supplement (NNS) on body composition participants. In a randomized, placebo-controlled trial, 55 participants (NNS: n = 28; placebo: n = 27) consumed either the NNS formulation comprising whey and pea protein, oats, flaxseed, spinach, beetroot, and chia or a placebo. Body composition (muscle mass, weight, BMI, fat %), oxygen saturation, and heart rate were measured at baseline and post-intervention. After 8 weeks, The NNS group showed a significant increase in muscle mass by 41.9%, rising from 12.96 kg to 18.41 kg (p = 0.000), while the placebo group only increased from 13.94 kg to 14.44 kg. Body weight in the NNS group decreased by 8.14 kg, from 76.54 kg to 68.40 kg (p < 0.001), whereas the placebo group gained 2.46 kg. BMI improved in the NNS group, dropping from 30.98 kg/m² to 25.7 kg/m² (p < 0.001), while remaining stable in the placebo group. Oxygen saturation increased from 95.85% to 98.62% (p = 0.001), and heart rate decreased from 76.00 bpm to 68.22 bpm (p = 0.004) in the NNS group. Fat percentage decreased from 30.63% to 27.11% (p = 0.0297). In conclusion, the novel natural multi-ingredient supplement significantly improved muscle mass, reduced body weight and BMI, and enhanced cardiopulmonary parameters, indicating its potential as a safe and effective nutritional strategy for improving body composition and performance in physically active individuals.